Menstrual Cycle Variation in MRI-Based Quantification of Intraluminal Gas in Women With and Without Dysmenorrhea - Oh, Hyeyoung; Ehrenpreis, Eli D.; Tu, Frank F.; Dillane, Katlyn E.; Garrison, Ellen F.; Leloudas, Nondas; Prasad, Pottumarthi V.; Hellman, Kevin M. (Frontiers in Pain Research, 2022)
Women frequently report increased bloating, flatulence, and pain during the perimenstrual period. However, it is unknown whether women have more intraluminal gas during menses. To evaluate whether pain-free women or women with dysmenorrhea have different amounts of intraluminal bowel gas during the menses, we utilized magnetic resonance imaging (MRI) to determine colonic gas volumes throughout the menstrual cycle. To avoid dietary influence, the participants were instructed to avoid gas-producing foods before their scheduled MRI. We verified the measurement repeatability across the reviewers and obtained an intraclass correlation coefficient of 0.92. There were no significant differences in intraluminal gas volume between menses and non-menses scans (p = 0.679). Even among the women with dysmenorrhea, there was no significant difference in the intraluminal gas volume between menses and non-menses (p = 0.753). During menstruation, the participants with dysmenorrhea had less intraluminal gas than participants without dysmenorrhea (p = 0.044). However, the correlation between the bowel gas volume and the pain symptoms were not significant (p > 0.05). Although increased bowel symptoms and bloating are reported in the women with dysmenorrhea during menses, our results do not support the hypothesis that increased intraluminal gas is a contributing factor. Although dietary treatment has been shown in other studies to improve menstrual pain, the mechanism responsible for abdominal symptoms requires further investigation. Our findings demonstrate that the intraluminal bowel gas volume measurements are feasible and are unaffected by menses under a controlled diet. The method described might prove helpful in future mechanistic studies in clarifying the role of intraluminal bowel gas in other conditions.